2007
DOI: 10.1111/j.1469-8749.2007.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune diseases in parents of children with infantile autism: a case—control study

Abstract: This register study compared the rates and types of autoimmune disease in the parents of 111 patients (82 males, 29 females; mean age at diagnosis 5y 5mo [SD 2y 6mo]) with infantile autism (IA) with a matched control group of parents of 330 children from the general population. All parents were screened through the nationwide Danish National Hospital Register. We inquired about 35 autoimmune diseases during an observation period of 27 years. At follow‐up the case and control mothers were identical in age (65y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 17 publications
6
67
1
Order By: Relevance
“…Although several reports have suggested an increased rate of autoimmune diseases in the mothers of children with autism, limitations in study design hinder interpretation and findings regarding specific autoimmune diseases have been inconsistent (26)(27)(28)(29). However, these data, together with the results from our current study, might suggest an overall alteration in the immune response in the mothers of children with autism during or around the time of pregnancy, not necessarily linked to a specific autoimmune condition or target organ.…”
Section: Discussioncontrasting
confidence: 55%
“…Although several reports have suggested an increased rate of autoimmune diseases in the mothers of children with autism, limitations in study design hinder interpretation and findings regarding specific autoimmune diseases have been inconsistent (26)(27)(28)(29). However, these data, together with the results from our current study, might suggest an overall alteration in the immune response in the mothers of children with autism during or around the time of pregnancy, not necessarily linked to a specific autoimmune condition or target organ.…”
Section: Discussioncontrasting
confidence: 55%
“…Parents of autistic children have higher rates of abnormal immune response (Comi et al 1999;Mouridsen et al 2007;Atladóttir et al 2009). Some research groups have argued that autism is an autoimmune disease (Ashwood and Van de Water 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to allergens can result in allergic reactions and in allergic and/or autoimmune disease (Astrakhan et al 2007;Valenta et al 2009;Lindelöf et al 2009). It has been reported that the mean probability of autoimmune disorders is greater in families with autism (Comi et al 1999;Mouridsen et al 2007;Atladóttir et al 2009). Autistic children could show abnormal immune responses and have elevated serum immunoglobulin E (IgE) and/or other Ig abnormalities (Magalhães et al 2009;Bakkaloglu et al 2008;Cohly and Panja 2005;Molloy et al 2006;Singer et al 2006;Enstrom et al 2009), which may provide a clue for treatment (Careaga et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Disease [18,[172][173][174][175] Rheumatoid arthritis Celiac disease Diabetes (Type 1) Ulcerative Colitis Psoriasis [176] Hypothyroidism/Hashimoto's thyroiditis ; [177,178] Rheumatic fever Idiopathic Thrombocytopenic Purpura (ITP) Myasthenia Gravis the more versatile ESC. The bone marrow contains two major types of stem cells, hematopoietic stem cells (HSC) and MSC.…”
Section: Type Of Stem Cellmentioning
confidence: 99%